The Role of Age, Sex, Body Mass Index, and Sport Type on the Dynamic Exertion Test in Healthy Athletes: A Cross-Sectional Study. Issue 5 (29th September 2022) - Sinnott, Aaron M.; Eagle, Shawn R.; Kochick, Victoria; Preszler, Jonathan; Collins, Michael W.; Sparto, Patrick J.; Flanagan, Shawn D.; Elbin, Robert J.; Connaboy, Christopher; Kontos, Anthony P.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: The dynamic exertion test (EXiT) was developed to help inform return to play after sport-related concussion, but some factors may threaten the internal validity of EXiT and affect clinical interpretation. Objective: To compare age, sex, BMI, and sport types across EXiT physiological [pre-EXiT and post-EXiT percentage of maximum heart rate (HR %max) and blood pressure (BP)], performance (change-of-direction task completion time and committed errors), and clinical [symptoms and rating of perceived exertion (RPE)] outcomes among healthy adolescents and adults. Study design: Cross-sectional. Methods: Eighty-seven participants ( F = 55, 37.4%) reported symptoms and RPE during the EXiT, which consists of a 12-minute treadmill running protocol, and the dynamic circuit, ball toss, box shuffle (SHUF) and carioca (CAR), zig zag (ZZ), proagility (PA), and arrow agility (AA) tasks. Independent samples t tests were conducted for pre-EXiT and post-EXiT HR %max and BP and change-of-direction task completion time and Mann–Whitney U tests for errors, symptoms, and RPE. A series of 1-way analysis of variance (ANOVAs) and Kruskal–Wallis H tests were conducted to compare collision, contact, and noncontact sport types. Results: Adolescents had lower completion time across AA ( P = 0.01) and male athletes lower than female athletes on CAR, ZZ, PA, and AA ( P < 0.04). Male athletes reported greater RPE after the SHUF, CAR, and AA ( P < 0.03). HR %max, errors, and symptoms were equivocal across all subgroups ( P > 0.05). Conclusion: Age and sex should be considered in the interpretation of performance and clinical, but not physiological, EXiT outcomes. The EXiT is a standardized exercise assessment and generalizable to healthy athletes.